THE PHENOMENON OF THE ABSORPTION AND DISPERSION OF SOLAR RADIATION IN THE ATMOSPHERE IS GOVERNED BY THE LAW OF WEAKENING. (Scientific journal of the Fergana State University, 2024)
This article provides information on changing the parameters in the law of weakening caused by the absorption and dispersion of solar radiation in the atmosphere. As a result of the absorption and dispersion of solar radiation in the atmosphere, it is weakened and the spectrum shifts towards longer wavelengths. A number of optical phenomena (the color of the sky, the color of the disk of the Sun and the Moon depending on the position relative to the horizon, etc.) are associated with the absorption and dispersion of solar radiation in the atmosphere